The effect of overlapping surgical scheduling on operating theatre productivity: a narrative review. (21st July 2022) - Pandit, J. J.; Ramachandran, S. K.; Pandit, M.
Summary: This article reviews the background to overlapping surgery, in which a single senior surgeon operates across two parallel operating theatres; anaesthesia is induced and surgery commenced by junior surgeons in the second operating theatre while the lead surgeon completes the operation in the first. We assess whether there is any theoretical basis to expect increased productivity in terms of number of operations completed. A review of observational studies found that while there is a perception of increased surgical output for one surgeon, there is no evidence of increased productivity compared with two surgeons working in parallel. There is potential for overlapping surgery to have some positive impact in situations where turnover times between cases are long, operations are short (<2 h) and where 'critical portions' of surgery constitute about half of the total operation time. However, any advantages must be balanced against safety, ethical and training concerns.